A Novel Plant Leaf Patch Absorbed With IL-33 Antibody Decreases Venous Neointimal hyperplasia - Xie, Boao; Bai, Xiche; Sun, Peng; Zhang, Liwei; Wei, Shunbo; Bai, Hualong (Frontiers in Bioengineering and Biotechnology, 2021)
Introduction: We recently showed that a decellularized leaf scaffold can be loaded with polylactic-co-glycolic acid (PLGA)-based rapamycin nanoparticles, this leaf patch can then inhibit venous neointimal hyperplasia in a rat inferior vena cava (IVC) venoplasty model. IL-33 plays a role in the neointimal formation after vascular injury. We hypothesized that plant leaves can absorb therapeutic drug solution and can be used as a patch with drug delivery capability, and plant leaves absorbed with IL-33 antibody can decrease venous neointimal hyperplasia in the rat IVC venoplasty model. Method: A human spiral saphenous vein (SVG) graft implanted in the popliteal vein was harvested from a patient with trauma and analyzed by immunofluorescence. Male Sprague-Dawley rats (aged 6–8 weeks) were used to create the IVC patch venoplasty model. Plant leaves absorbed with rhodamine, distilled water (control), rapamycin, IL-33, and IL-33 antibody were cut into patches (3 × 1.5 mm2) and implanted into the rat IVC. Patches were explanted at day 14 for analysis. Result: At day 14, in the patch absorbed with rhodamine group, immunofluorescence showed rhodamine fluorescence in the neointima, inside the patch, and in the adventitia. There was a significantly thinner neointima in the plant patch absorbed with rapamycin (p = 0.0231) compared to the patch absorbed with distilled water. There was a significantly large number of IL-33 (p = 0.006) and IL-1β (p = 0.012) positive cells in the human SVG neointima compared to the human great saphenous vein. In rats, there was a significantly thinner neointima, a smaller number of IL-33 (p = 0.0006) and IL-1β (p = 0.0008) positive cells in the IL-33 antibody-absorbed patch group compared to the IL-33-absorbed patch group. Conclusion: We found that the natural absorption capability of plant leaves means they can absorb drug solution efficiently and can also be used as a novel drug delivery system and venous patch. IL-33 plays a role in venous neointimal hyperplasia both in humans and rats; neutralization of IL-33 by IL-33 antibody can be a therapeutic method to decrease venous neointimal hyperplasia.